2009
DOI: 10.1038/nrd2827
|View full text |Cite
|
Sign up to set email alerts
|

Capturing adenylyl cyclases as potential drug targets

Abstract: Cyclic AMP (cAMP) is an important intracellular signalling mediator. It is generated in mammals by nine membrane-bound and one soluble adenylyl cyclases (ACs), each with distinct regulation and expression patterns. Although many drugs inhibit or stimulate AC activity through the respective upstream G-protein coupled receptors (for example, opioid or beta-adrenergic receptors), ACs themselves have not been major drug targets. Over the past decade studies on the physiological functions of the different mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
239
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(244 citation statements)
references
References 164 publications
3
239
0
2
Order By: Relevance
“…Pharmacological sAC modulation has potential therapeutic applications (19)(20)(21)39), and because artificially manipulating the natural activator bicarbonate is problematic in physiological systems, sAC-selective modulators would facilitate in vivo studies. In tmAC, the space corresponding to the hydrophilic sAC BBS between Arg176 (Asn in tmAC) and Lys95 is blocked by a hydrophobic residue (Leu438 in tmACV-C 1 , interacting with Phe338).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological sAC modulation has potential therapeutic applications (19)(20)(21)39), and because artificially manipulating the natural activator bicarbonate is problematic in physiological systems, sAC-selective modulators would facilitate in vivo studies. In tmAC, the space corresponding to the hydrophilic sAC BBS between Arg176 (Asn in tmAC) and Lys95 is blocked by a hydrophobic residue (Leu438 in tmACV-C 1 , interacting with Phe338).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, sAC acts as a CO 2 /HCO 3 − /pH sensor in processes such as sperm activation (15), acid-base homeostasis (16), and various metabolic responses (10,17,18). sAC has also been implicated in skin and prostate cancer and as a target for male contraceptives (19)(20)(21).…”
mentioning
confidence: 99%
“…By contrast, adenosine-derived cAMP signaling can attenuate many of these effects (5). Moreover, cAMP produced by different adenylyl cyclases (ACs) has different cardiac effects: AC5-derived cAMP is detrimental, whereas AC6-derived cAMP is protective in pathological cardiac remodeling (6). cGMP is generated from both the soluble and particulate guanylyl cyclases (GCs), and many studies have shown negative inotropic and cardioprotective effects (7,8) from cardiac cGMP signaling.…”
mentioning
confidence: 99%
“…8 To begin to evaluate the role of individual AC isoforms in PKD renal disease, we have now studied mouse models of polycystin-1 deficiency with or without AC6 deficiency. Given that no specific AC isoform inhibitors exist (although this area represents an active area of drug development 9 ), a genetic engineering approach was used. We previously reported a mouse model of PKD by selectively deleting the Pkd1 gene in CD principal cells.…”
mentioning
confidence: 99%